Medium cut-off membrane expanded hemodialysis for Lithium removal: a case report - Pérez del Valle, Katia M.; Moran Magro, María; Gaitán Tocora, Daniel; Boldoba, Nerea Begoña; Benito Puncel, Carmen; Silva Obregón, Alberto; Rodríguez Palomares, José R.; de Arriba de la Fuente, Gabriel (Frontiers in Toxicology, 2025)
BackgroundLithium remains a first-line treatment for bipolar disorder, though its narrow therapeutic window poses a significant risk of toxicity. Severe intoxication can lead to neurologic, renal, gastrointestinal, and endocrine complications. Extracorporeal therapies are the mainstay in managing life-threatening cases, particularly when serum concentration exceed 4.0 mmol/L or when renal function is impaired. Intermittent hemodialysis (HD) is the recommended extracorporeal treatment due to lithium’s low molecular weight and minimal protein binding. Expanded hemodialysis (HDx) with medium cut-off (MCO) membranes, designed to enhance solute clearance, may represent a promising alternative.Case ReportWe present a case of acute lithium intoxication in a 48-year-old male with a history of recurrent suicidal behavior and chronic lithium therapy. The patient arrived at the emergency department in a deep coma (GCS 3), with a serum lithium concentration of 4.5 mmol/L and preserved renal function. He underwent two intermittent HDx sessions using a Theranova® TH-400 MCO membrane. Serum lithium concentration declined to 1.6 mmol/L after the first session and progressively to 0.1 mmol/L within 72 h. No treatment-related complications were observed.ConclusionThis case described the potential utility of HDx with the MCO membrane (Theranova® 400) in managing severe lithium poisoning, achieving effective and sustained drug clearance. While HDx-MCO may offer a viable alternative to conventional HD, especially in settings where enhanced solute removal is desirable, further studies are needed to determine its efficacy and clinical role in lithium toxicity management.